Cutaneous Osteoblastic Osteosarcoma: Report of 2 New Cases Integrated With SATB2 Immunohistochemistry and Review of the Literature. (November 2016) - Falconieri, Giovanni; Cataldi, Palmina; Kavalar, Rajko; Štitič, Vesna; Luzar, Boštjan
Abstract : Abstract: We report 2 cases of primary dermal osteosarcoma. The patients were an 88-year-old man and a 72-year-old man complaining of masses occurring in the ear pavilion and the palm, deemed suspicious for basal cell carcinoma and metastatic colonic carcinoma, and were treated by resection. Microscopically, both featured a dermal lesion mostly composed of atypical spindle cells within a fibrous to hyaline matrix often showing mineralization. Osteoid material was rimmed by atypical tumor cells and was also associated with osteoclast-like giant cells. Tumor cells were positive for SATB2 and negative for markers of epithelial (low-molecular and high-molecular weight cytokeratins, epithelial membrane antigen, p63), melanocytic (S100 protein, HMB45, Melan A), and skeletal/smooth muscle differentiation (desmin, myogenin). No further therapy has been administered. Follow-up at 6 (case 1) and 8 months (case 2) was uneventful. A brief differential diagnosis discussing cutaneous tumors capable of showing osseous differentiation is summarized, along with a review of the pertinent literature. The specificity and sensitivity of SATB2 is also shortly addressed.